2011
DOI: 10.1108/07378831111189822
|View full text |Cite
|
Sign up to set email alerts
|

Personal information management (PIM), reference management and mind maps: the way to creative librarians?

Abstract: Please note, this is not the final version that appeared in Library Hi Tech AbstractPurpose -The column explores the potential of personal information management (PIM) and reference management. This contribution focuses on combining the use of PIM and reference management software with mind maps to stimulate the creative and innovative use of information collected. Following a brief review of the literature on the topic per se, awareness is raised of appropriate software and the potential of mind maps.Design/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(14 reference statements)
1
9
1
1
Order By: Relevance
“…Mind-mapping features could help students with this challenge. As noted by Fourie (2011b), mind mapping software offers several benefits for managing personal information and can be useful for organizing ideas, synthesizing information and identifying gaps in research. While some students indicated that they were extremely interested in this option, interest in mind-mapping features were not as highly desired as some other PDF management features.…”
Section: Challengesmentioning
confidence: 99%
“…Mind-mapping features could help students with this challenge. As noted by Fourie (2011b), mind mapping software offers several benefits for managing personal information and can be useful for organizing ideas, synthesizing information and identifying gaps in research. While some students indicated that they were extremely interested in this option, interest in mind-mapping features were not as highly desired as some other PDF management features.…”
Section: Challengesmentioning
confidence: 99%
“…Files, website addresses; Boardman & Sasse, 2004) and is frequently cased in terms of an individual's ability to manage information in fulfillment of their various life roles such as parent, employee, student, etc. (Fourie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is an integrated tool of information management providing support to workflows of scientific research in any given area. Fourie suggested considering reference management software as a specific type of personal information manager, with the ability to combine the information they contain with organizations and visualizations such as Topic Maps (Fourie, 2011). Hull, Petiffer and Kell (2008) went further when reviewing the integration of digital libraries into web-based reference managers.…”
Section: Discussionmentioning
confidence: 99%